Best practices for replicability, reproducibility and reusability of computer-based experiments exemplified by model reduction software - Jörg Fehr; Jan Heiland; Christian Himpe; Jens Saak (AIMS Mathematics, 2016)
Over the recent years the importance of numerical experiments has gradually been more recognized. Nonetheless, su cient documentation of how computational results have been obtained is often not available. Especially in the scientific computing and applied mathematics domain this is crucial, since numerical experiments are often employed to verify the proposed hypothesis in a publication. This work aims to propose standards and best practices for the setup and publication of numerical experiments. Naturally, this amounts to a guideline for development, maintenance, and publication of numerical research software. Such a primer will enable the replicability and reproducibility of computer-based experiments or published results and also promote the reusability of the associated software.